PENERAPAN MODEL PEMBELAJARAN STORY TELLING PADA KEMAMPUAN SPEAKING MAHASISWA UNIVERITAS ISLAM TRIBAKTI LIRBOYO KEDIRI - Rasyidah, Umi Imtitsal (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
English is an international language spoken all over the world. English is also one of the disciplines that has been taught since the end of the school to become one of compulsory courses given in the early semesters. To be able to improve speaking skills educators can use the learning model of storytelling or chanting. The application of storytelling to improve the ability to speak English can be one of the alternatives can also be applied. The research is aimed at improving English speaking skills through Storytelling methods in New Students of the Faculty of Dakwah, Ushuluddin, and Psychology of the Islamic University of Tribakti Lirboyo Kediri. English is an international language spoken almost all over the world. English is also one of the compulsory courses programmed by graduates in the first semester. Being able to speak or communicate actively and smoothly in English is also an extra point for students in the age of globalization. This research uses qualitative methods with descriptive types. The results show an improvement in the ability to speak English through the application of the Storytelling learning model.